Literature in EFL/ESL Classroom: Integrating Conventional Poetry as Authentic Material - Islam, Muhammmad Reazul (International Journal of Language and Literary Studies, 2022)
The paper aims to explore how poetry and poetic devices function as authentic sources and as required materials for teaching and learning English as a second language or a foreign language. It affirms that different modes of poetry, for example, tongue twisters, children’s rhymes, sonnets, short and long poems, etc., can be stimulating, appealing, and above all, the natural material to the EFL/ESL classrooms. Through an interactive and integrated teaching approach, the paper intends to promote and motivate learners and teachers to use poetry as a functional source of literature for teaching English as a target language. Simultaneously, the study emphasises the constructive function of literature in developing a language learning process. The paper represents general sources or materials widely used in EFL/ ESL classrooms for decades. It proclaims why including authentic or natural material is inevitable to revitalize the language learning process. It profoundly claims that using conventional poetry in EFL/ESL classrooms can empower the teaching pedagogy with its own stylistic and pragmatic features. To focus on the pedagogical dimension of poetry in second language classrooms, the article demonstrates how a poem can relate to and integrate to enhance the English language and covers the four core language skills, grammar, and vocabulary through a series of interactive classroom activities.